Effect of Exchange Rate Changes on Exports and Imports in Indonesia - Loso Judijanto; Marita Damanik (PT. Anagata Sembagi Education, 2025)
This study analyzes the impact of exchange rate fluctuations on Indonesia’s trade performance, focusing on exports and imports. Using a quantitative approach with econometric analysis, the research applies multiple linear regression to examine the relationship between exchange rates and trade. The findings reveal that exchange rate depreciation does not always enhance exports as commonly expected; instead, it may increase import costs, affecting overall trade balance. While a weaker Rupiah can make Indonesian goods more affordable in global markets, the extent of its impact depends on factors such as production capacity, global demand, and trade policies. The statistical tests confirm that exchange rate movements have a significant influence on trade performance, with the model demonstrating strong explanatory power. These results highlight the crucial role of exchange rate stability in maintaining a competitive and sustainable trade environment. The study provides valuable insights for policymakers, businesses, and researchers in developing strategies to mitigate risks associated with exchange rate fluctuations and strengthen Indonesia’s position in international trade.